Analisis Gerakan Politik Hijau WALHI Melalui Media Sosial Instagram dalam Mewujudkan Kesadaran Lingkungan - Wahyu Kartiko Utami (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
This research analyzes the role of Instagram social media in shaping digital public space for the Indonesian Forum for the Environment (WALHI) environmental movement. The main focus of this study is how the @walhi.national account mobilizes discourse, solidarity, and collective action in contemporary ecological issues, with a theoretical approach that refers to Sidney Tarrow's Cycle of Contention framework (1994). The analysis shows that WALHI utilizes Instagram as a means to respond to political moments and ecological crises, such as the Rempang conflict (2023) and the rejection of the Trenggalek gold mine (#TolakTambangTrenggalek). The initial phase was characterized by the outbreak of political opportunities through controversial policies. WALHI then mobilized, framed and diffused action through the spread of visual narratives and hashtag campaigns that expanded solidarity. In the final phase, WALHI as an organization has undergone a transformation process from a field-based advocacy movement to a professional, strategic and technology-adaptive digital actor. WALHI through @walhi.national together with various parties such as volunteers, academics, communities and the public have contributed to encouraging institutional advocacy and redrafting policy discourse related to the environment. This study concludes that social media is not only a tool for information dissemination, but also a field of political articulation that can strengthen or challenge power structures in the contestation cycle. Instagram becomes an important arena for WALHI in maintaining moral legitimacy and expanding the environmental movement to a more inclusive and connected level.